2015
DOI: 10.1200/jco.2015.33.7_suppl.512
|View full text |Cite
|
Sign up to set email alerts
|

Societal costs after renal cancer surgery.

Abstract: 512 Background: The hospital costs of radical or partial nephrectomy for treatment of confirmed or suspected renal cell carcinoma have been well described. We sought to estimate a previously unreported societal cost of renal cancer surgery by assessing surgery-related time off work (TOW) taken by patients and their caretakers. Methods: To a cohort of 315 subjects enrolled in an IRB-approved prospective renal quality-of-life study who underwent radical or partial nephrectomy at our institution, we administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With the advances of minimally invasive surgery, it is possible to reduce the hospitalization time and costs, not only of the surgery itself but the social costs, as described by the series of Chang et al they demonstrated a medium withdrawal time of 35 days from work, from 7 to 92 days, with a medium salary loss of US$ 10.152 in the United States ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the advances of minimally invasive surgery, it is possible to reduce the hospitalization time and costs, not only of the surgery itself but the social costs, as described by the series of Chang et al they demonstrated a medium withdrawal time of 35 days from work, from 7 to 92 days, with a medium salary loss of US$ 10.152 in the United States ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed with the 21-item Beck's Depression Inventory [39]. The total sum score of the scale ranges from 0 to 63 and was further categorized into the following: No depression (0-13), mild depression (14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), or severe depression . The BDI is a widely used valid measure of depression [40] with a Cronbach's alpha value of 0.90 found in a population of women with breast cancer [41].…”
Section: Health-related Variables: Depression Fatigue and Performancmentioning
confidence: 99%
“…Thus, to most people, job loss and sickness absence have considerable negative consequences [11]. Furthermore, the 1 financial burden of work disability due to cancer is high for society [15,16]. Hence, improving the work ability and the process of return to work (RTW) for the steadily increasing number of people with current or previous cancers is of major importance.…”
Section: Introductionmentioning
confidence: 99%